First-principles study of adhesion strength and stability of the TiB2/TiC interface in composite materials. Issue 2 (1st February 2018) - Song, Xiaojie; Han, Ye; Wang, Xiao; Liu, Weihui; Wu, Jie; Cui, Hongzhi
Abstract: The properties of a TiC(0 1 0) surface, a TiB2 (0 1 1 ¯ 0) surface, and TiC(0 1 0)/TiB2 (0 1 1 ¯ 0) interfaces were investigated by first-principles calculations. The work of adhesion ( W ad ), the interface energy (γ int ), and the electronic structure of the interfaces were determined. The results show that the C-BS1-B1, C-TS-B2, and Ti-BS1-B1 interfaces are the most stable interfaces. Among all models, the C-TS-B2 interface is most stable and exhibits the highest W ad value (4.77 J/m 2 ) and the lowest γ int value (1.12 J/m 2 ). All three stable interfaces exhibit strong covalent bonding due to the interfacial C-sp and B-sp orbital hybridization; the stable interfaces investigated in this study are as stable as the TiC(1 1 1)/TiB2 (0 0 0 1) interface reported in a previous study.